2010
DOI: 10.1007/s12070-010-0002-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of two cefazolin prophylactic protocols in oncologic surgery of the larynx: A randomized trial

Abstract: Objective Patients who need major head and neck surgery like laryngectomy are at risk of postoperative wound infection. Although the role of antibiotics in prophylaxis of clean contaminated head and neck surgery has been well documented, controversy exists in the optimal antibiotic regimen. Results No wound infection was detected in either 2-day group, and 3 (6.7%) in the 5-day group. There was between two groups. Methods In two tertiary referral hospitals (Imam ConclusionWe conclude that a 2-day perioperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
(43 reference statements)
1
5
0
Order By: Relevance
“…Surgeons tend to prolong postoperative ABP in patients with an increased risk of complications, e.g., after a total laryngectomy with flap reconstruction or after previous radiotherapy. Various studies fail to show a beneficial effect of long-term prophylaxis in patients undergoing laryngectomy, free flap reconstruction, or in patients with other risk factors including diabetes, increased BMI, malnutrition, or a tracheotomy [7,22,26]. Our findings are consistent with recent systematic reviews by Patel et al [52] and Jethwa and Khariwala [53], and also concur largely with the conclusions of a recent meta-analysis of existing guidelines [12].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Surgeons tend to prolong postoperative ABP in patients with an increased risk of complications, e.g., after a total laryngectomy with flap reconstruction or after previous radiotherapy. Various studies fail to show a beneficial effect of long-term prophylaxis in patients undergoing laryngectomy, free flap reconstruction, or in patients with other risk factors including diabetes, increased BMI, malnutrition, or a tracheotomy [7,22,26]. Our findings are consistent with recent systematic reviews by Patel et al [52] and Jethwa and Khariwala [53], and also concur largely with the conclusions of a recent meta-analysis of existing guidelines [12].…”
Section: Discussionsupporting
confidence: 90%
“…These findings are confirmed by Sepehr et al [22], who also found no SSI rate reduction after prolonged prophylaxis in patients with malnutrition (p = 1.00). Also in the specific high-risk group of laryngectomy patients, 5 days of cefazolin had no advantage over 2 days of prophylaxis: no difference in fistula development rate was observed (p [ 0.05) [26]. Likewise, Busch et al [7] also found that the duration of prophylaxis did not influence the rate of fistula formation after major procedures.…”
Section: Prolonged Antibiotic Course In Patients With Otherwise Incrementioning
confidence: 94%
See 1 more Smart Citation
“…05) 183 . Multiple additional studies consistently show that duration of antibiotics for greater than 24 hours and the use of extended preoperative antibiotic use have no added benefit 139,140,143‐145,148,159,184‐194 …”
Section: Discussionmentioning
confidence: 99%
“…183 Multiple additional studies consistently show that duration of antibiotics for greater than 24 hours and the use of extended preoperative antibiotic use have no added benefit. 139,140,[143][144][145]148,159,[184][185][186][187][188][189][190][191][192][193][194] Microvascular free flaps are a unique entity within cleancontaminated surgery. Several authors have found clindamycin to be inferior to other regimens and suggested the need to consider the addition of a second antibiotic to improve coverage of aerobic gram-negative bacteria.…”
Section: Clean Head and Neck Surgery Recommendationmentioning
confidence: 99%